Spiro‐Indole‐Coumarin Hybrids: Synthesis, ADME, DFT, NBO Studies and In Silico Screening through Molecular Docking on DNA G‐Quadruplex. Issue 11 (19th March 2020) - Khanna, Leena; Singhal, Sugandha; Jain, Subhash C.; Khanna, Pankaj
Abstract: New series of hybrids were synthesized by combination of 4‐hydroxycoumarin with spiro[indol‐indazole‐thiazolidine]‐diones and spiro[indol‐pyrazole‐thiazolidine]‐diones, via hitherto unknown Schiff bases. The effects of substituents, such as ‐F, ‐Br and ‐CH3, on the crucial characteristics pertaining to the hybrids were investigated through computational studies. In silico or virtual screening through molecular docking studies on the library of 22 compounds, including reference compounds, precursors, non‐hybrid and hybrid derivatives, was performed on DNA G‐quadruplex of the human genome. All six freshly synthesized hybrids showed high binding energy as compared to non‐hybrids as well as reference compounds. The presence of substituents at 5‐position of indole enhanced the binding tendency of the ligand. ADME studies indicated good oral bioavailability and absorption of these compounds. Density Functional Theory (DFT) calculations of hybrids were done at B3LYP/6‐311G++(d, p) level of computation. Their HOMO and LUMO energy plots reflected the presence of high charge transfer and chemical potential. Natural bond order (NBO) calculations predicted hyperconjugative interactions. The Molecular Electrostatic Potential (MEP) surface plots showed possible electrophilic and nucleophilic attacking sites of the hybrids. Compound 10 a (5‐fluoro‐spiro[indol‐indazole‐thiazolidine]‐dione‐coumarin hybrid), on the basis of global reactivity descriptors, was filtered to be chemically most reactive with the highest binding energy of −8.23 kcal/mol with DNA G‐quadruplex. The synthesized hybrid coumarin derivatives in correlation with theoretical docking studies validate that hybrid derivatives are more reactive compared to their non‐hybrid counterparts. Abstract : Six new hybrids, spiro[indol‐indazole‐thiazolidine]‐dione‐coumarin hybrids (10a‐c) and spiro[indol‐pyrazole‐thiazolidine]‐dione‐coumarin hybrids (12a‐c), were synthesized successfully via hitherto unknown Schiff bases. These compounds were virtually screened for their drug likeliness, toxicity and docking interactions with DNA G‐quadruplex (compared with library of known compounds). The Density Functional Theory (DFT) electronic reactivity descriptors, depicted their high chemical reactivity and the Molecular Electrostatic Potential (MEP) and contour plots described their potential active sites. Further, the detailed Natural bond order (NBO) analysis of these hybrids suggested hyperconjugative interactions.